PERUBAHAN MORFOLOGIS DALAM BAHASA GAUL : ANALISIS PROSES PEMBENTUKAN KATA DI MEDIA SOSIAL TIKTOK - Anggi Saputra; Syafi’ Junadi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study examines the changes in word forms in slang used on the TikTok social media platform. The analysis shows that the most frequent morphological processes include affixation, reduplication, composition, acronymization, and conversion. Each of these processes produces new variations that increase the non-standard vocabulary of Indonesian, with creative, concise characteristics, and in accordance with the digital culture of the younger generation. Affixation appears in words such as ngakak, reduplication in the form of anjir-anjir, composition in terms such as cosplay, conversion in the word respect and acronymization in abbreviations such as salfok. This phenomenon shows that slang on TikTok not only functions as a means of communication, but also as a medium for expressing social identity in online communities. This finding emphasizes the need to understand the development of language in the digital era as part of the social and cultural dynamics of modern society.